Special cementing material for microwave heating concrete as well as preparation method and application of special cementing material
By developing a gelling material for microwave heating concrete made of solid waste, the problem of low efficiency of existing microwave deicing technology has been solved, and efficient deicing, low cost and environmentally friendly results have been achieved.
Patent Information
- Application Number
- CN202510007693.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing microwave deicing technology is inefficient and difficult to meet the needs of deicing operations in actual work.
Developed a gelling material for microwave heating concrete, made of specific solid waste, with excellent compressive strength, low resistivity and high microwave heating efficiency. The material improves the microwave heating performance of concrete through specific assembly distribution ratios and process treatment.
It realizes efficient microwave heating of gelled materials, improves deicing efficiency, reduces costs and environmental pollution, and improves the compressive strength and conductive properties of the materials.
Smart Images

Figure CN119683961A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and more specifically to a special cementitious material for microwave-heated concrete and a preparation method and application thereof. Background Art
[0002] China has a vast territory and complex meteorological conditions. Some areas in the north are in winter for a long time, and some high-altitude areas are also in a freezing period all year round. Due to the influence of long-term low temperature, the residual rainwater on the road surface condenses into ice, which greatly reduces the friction factor of the road surface and brings great pressure to traffic safety. At present, the three commonly used deicing methods in deicing operations are removal method, melting method and suppression method, which have played a certain role in clearing ice on the road surface, but there are also some problems in use, such as high-temperature airflow causing great damage to the road surface, low energy utilization rate, and serious environmental pollution. Therefore, in order to adapt to the development needs of road traffic in the new era and improve road security performance, it is imperative to develop a new deicing method.
[0003] Microwave deicing technology is a new deicing technology developed in recent years. Compared with traditional deicing methods, it has many advantages: high ice removal rate, good thick ice removal effect, greening and environmental protection, etc. It has a good application prospect in winter road deicing. The microwave deicing method has been proposed since the 1970s, but it has not been promoted and applied in actual work. This is mainly because the microwave deicing efficiency is too low to meet the needs of deicing operations in actual work.
[0004] Therefore, in order to improve the deicing efficiency of microwave deicing methods, Chinese and foreign researchers have conducted extensive research on microwave heating technology and microwave deicing efficiency. In foreign countries, in the Strategic Highway Research Program (SHRP) implemented by the Federal Highway Administration of the United States, Lindroth et al., Ye et al., Gao et al., and the Natural Resources Research Institute (NRRI) in Minnesota, USA, have conducted in-depth research on microwave deicing technology, but due to the low efficiency of microwave deicing, it is rarely used in actual operations. Domestic research on microwave deicing technology has also been conducted to a certain extent, but most of them focus on the development of microwave heating devices, and there is relatively little research on the mechanism of microwave heating.
[0005] In 2003, Li Xiao et al., Guan Minghui et al. first proposed the idea of using microwave deicing technology for road deicing in China, designed a microwave deicing vehicle model, and applied for two patents for microwave deicing. In 2012, Guo Dedong et al. used magnetite with strong microwave absorption ability to replace ordinary aggregates, studied the proportion design of magnetite asphalt concrete materials, the heating mechanism of microwave and magnetite, and the microwave deicing efficiency and deicing process of magnetite asphalt pavement. In 2016, Lu Song et al. studied the microwave deicing performance of airport concrete pavement and analyzed the influence of microwave frequency and pavement material characteristics on the microwave deicing efficiency of airport pavement. In general, existing research mainly studies the materials, microwave frequencies, and microwave radiator designs of microwave deicing, but lacks analysis of the application technology of microwave deicing methods in actual use, which requires in-depth research on the height of the radiation port, and the experimental equipment used in some studies is relatively simple and lacks system design.
[0006] In order to better solve the application difficulties of microwave heated concrete in road deicing, the present invention provides a special cementitious material for microwave heated concrete and a preparation method and application thereof. The cementitious material is made of specific solid waste and has excellent compressive strength, low resistivity and high microwave heating efficiency, and can be used to prepare microwave heated concrete. Summary of the invention
[0007] The purpose of the present invention is to provide a special cementitious material for microwave-heated concrete and a preparation method and application thereof. The cementitious material is made from specific solid waste and has excellent compressive strength, low resistivity and high microwave heating efficiency, and can be used to prepare microwave-heated concrete.
[0008] The present invention is achieved through the following technical solutions: A special cementitious material for microwave heating concrete, comprising the following components by weight: 5-10 parts of fly ash; 30-45 parts of steel slag; 30-45 parts of high iron phase silicate cement clinker; 5-10 parts of high belite sulfate cement clinker; 5-10 parts of gypsum; 2-4 parts of waste residue; 3-5 parts of solid waste; Graphene 0.1-0.5 parts; Palmitic acid 0.5-1.5 parts; Water reducing agent 0.5-1.5 parts; The content of tetracalcium aluminate in the high-iron phase silicate cement clinker is greater than 20%, and the content of tricalcium aluminate is less than 3%; The content of dicalcium silicate in high-belite sulfate cement clinker is greater than 45%, and the content of calcium sulfoaluminate is 30-50%.
[0009] Furthermore, the fly ash is the bottom ash collected by the flue gas purification system during the waste incineration process and the bottom ash settled at the bottom of the flue and chimney. The specific surface area of the fly ash is 600-1000m 2 / kg, calcium content is greater than 35%.
[0010] Furthermore, the gypsum is desulfurized gypsum, and the content of calcium sulfate dihydrate in the desulfurized gypsum is greater than 94%, and the content of calcium carbonate is greater than 1%.
[0011] Furthermore, the waste residue is waste residue generated during alkali production or alkali treatment, and the content of sodium hydroxide and potassium hydroxide in the waste residue is greater than 5%.
[0012] Furthermore, the solid waste is dust collected during limestone crushing production, and the specific surface area of the solid waste is 500-800m 2 / kg.
[0013] Furthermore, the graphene is multilayer graphene with a layer number greater than 15, and the particle size of the graphene is 0.05-2 mm.
[0014] Furthermore, the palmitic acid is industrial grade palmitic acid with a melting point less than 63° C. and a purity greater than 98%.
[0015] Furthermore, the water reducing agent is a polycarboxylate water reducing agent with a water reducing rate greater than 45%.
[0016] A method for preparing the aforementioned microwave-heated cementitious material for concrete comprises the following steps: Ⅰ. Prepare the raw materials according to the aforementioned composition ratio and set aside; Ⅱ. Take steel slag, high iron phase silicate cement clinker, high belite sulfate cement clinker and palmitic acid and put them into steel ball mill for grinding until the specific gravity is 270-320m 2 / kg, 45μm sieve residue is greater than 15%, and mixed material 1 is obtained; III. Take the waste residue and graphene and mix them thoroughly, add water until the mixed material is covered, stir thoroughly for 8-12 hours, and then directly dry to obtain the second mixed material for standby use; IV. Take fly ash, gypsum, solid waste and water reducing agent, and fully mix them with mixture 1 and mixture 2 to obtain a special cementitious material for microwave heating.
[0017] The use of a special cementitious material for microwave heating as described in any of the preceding claims in the preparation of microwave-heated concrete.
[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. In the present invention, a large amount of solid waste such as fly ash, steel slag, desulfurized gypsum, caustic soda waste residue, limestone crushing dust, etc. is utilized, which greatly reduces the cost of cementitious materials and realizes energy conservation and emission reduction. In addition, by controlling the grinding particle size, the energy consumption of clinker grinding is reduced, and fly ash and limestone crushing dust are used to supplement the fine particles in the cementitious materials, so as to realize the continuous gradation of cementitious materials, improve the density, reduce harmful pores, ensure the strength, and reduce the water demand and the amount of water reducing agent.
[0019] 2. In the present invention, the energy consumption of grinding is further reduced by adding palmitic acid to assist grinding during the grinding process. As the temperature rises during the grinding process, the palmitic acid undergoes phase change and absorbs heat, thereby reducing the material temperature, ensuring the grinding efficiency, and reducing safety hazards. Palmitic acid can also help concrete prevent corrosion, improve sealing performance, and enhance the comprehensive performance of concrete.
[0020] 3. In the present invention, calcium sulfoaluminate in high-belite sulfoaluminate cement clinker is used to provide early strength, reduce curing time and curing cost, high-iron phase silicate cement clinker is used to improve durability and supplement late strength, sulfate excitation and alkali excitation are used to jointly act on fly ash and steel slag to supplement strength, and graphene is combined to form fibers to improve crack resistance and overall strength, thereby achieving a cementitious material with high early strength, guaranteed late strength, good durability and strong crack resistance; in addition, high-belite sulfoaluminate cement data and high-iron phase ordinary silicate cement clinker both have good high temperature resistance, and can also ensure overall stability during the heating process.
[0021] 4. In the present invention, graphene is intercalated with caustic soda waste slag, so that sodium hydroxide, sodium carbonate, sodium chloride and oxides such as iron and aluminum in the caustic soda waste slag enter the graphene interlayer. The treated graphene has ionic polarity. In addition, fly ash, high-iron phase ordinary silicate cement clinker, high-belite sulphoaluminate cement clinker, steel slag, desulfurized gypsum and caustic soda waste slag are all polar materials, which can be used to achieve self-heating of concrete, melt ice and snow or be applied in other scenarios requiring heating through microwaves.
[0022] 5. In the present invention, graphene itself can achieve good electrical conductivity through electronic conduction, and after combined with oxidation intercalation treatment, it has ionic conductivity. Fly ash, limestone powder, etc. enter the graphite layer, and react with the alkali between the layers to fix the interlayer ions, thereby achieving conductive stability. Other substances such as steel slag and fly ash also have certain electrical conductivity. The prepared gelling material has good electrical conductivity, and electric heating can be used as compensation to ensure the heating performance of the material together with microwave heating.
[0023] Sixth, in the present invention, the phase change function of palmitic acid can also be used to reduce energy consumption and ensure the long-term stability of concrete during the heating process. Palmitic acid is heated to melt during the off-peak period, absorbing a large amount of heat for storage. During the peak period of electricity consumption, palmitic acid can solidify and release heat, reducing the working time during the peak period of electricity consumption; at the same time, when the temperature is high, palmitic acid melts, leaving space for the deformation generated when the concrete is heated, which can prevent the concrete from cracking. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of graphite intercalation. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0026] In the present invention, the content of tetracalcium aluminoferrate in the high iron phase silicate cement clinker is greater than 20%, and the content of tricalcium aluminate is less than 3%. In the following embodiments, the high iron phase silicate cement clinker is illustrated by taking ordinary silicate cement clinker with a tetracalcium aluminoferrate content of 22% and a tricalcium aluminate content of 2.8%.
[0027] In the present invention, the content of dicalcium silicate in the high belite sulfate cement clinker is greater than 45%, and the content of calcium sulfoaluminate is 30-50%. In the following embodiments, the high belite sulfate cement clinker is taken as an example of the high belite sulfoaluminate cement clinker produced by Jiahua Special Cement Co., Ltd.
[0028] In the present invention, the fly ash is the bottom ash collected by the flue gas purification system during the waste incineration process and the bottom ash settled at the bottom of the flue and chimney. The specific surface area of the fly ash is 600-1000m 2 / kg, and the calcium content is greater than 35%. In the following embodiments, fly ash is taken as fly ash produced by Everbright Environmental Energy (Leshan) Co., Ltd. for example.
[0029] In the present invention, the gypsum is desulfurized gypsum, and the content of calcium sulfate dihydrate in the desulfurized gypsum is greater than 94%, and the content of calcium carbonate is greater than 1%. In the following embodiments, the desulfurized gypsum of Sichuan Desheng Iron and Steel Co., Ltd. is used as an example for illustration.
[0030] In the present invention, the waste residue is waste residue produced in the process of alkali production or alkali treatment, and the content of sodium hydroxide and potassium hydroxide in the waste residue is greater than 5%. In the following embodiments, the waste residue is illustrated by taking the waste residue with a sodium hydroxide and potassium hydroxide content of about 8% as an example.
[0031] In the present invention, the solid waste is dust collected during limestone crushing production, and the specific surface area of the solid waste is 500-800m 2 In the following examples, the solid waste has a specific surface area of about 750m 2 / kg of limestone dust as an example.
[0032] In the present invention, the graphene is a multilayer graphene with a number of layers greater than 15, and the particle size of the graphene is 0.05-2 mm. In the following embodiments, the graphene is illustrated by taking the multilayer graphene produced by Nantong Qiangsheng Graphene Technology Co., Ltd. as an example.
[0033] In the present invention, the palmitic acid is industrial grade palmitic acid with a melting point of less than 63° C. and a purity of more than 98%. In the following embodiments, the palmitic acid is an industrial grade palmitic acid supplied by Shanghai Kabo Industry & Trade Co., Ltd., for example.
[0034] In the present invention, the water reducing agent is a polycarboxylate water reducing agent with a water reducing rate greater than 45%. In the following embodiments, the water reducing agent is taken as Sika 556P to illustrate the effect of this solution.
[0035] Example 1 A special cementitious material for microwave-heated concrete relates to the technical field of building materials and comprises the following components according to the mass fractions of each group in Table 1.
[0036] The preparation method of the special cementitious material for microwave heating concrete comprises the following steps: Ⅰ. Prepare the raw materials according to the composition ratio of each group in Table 1 and set aside; Ⅱ. Put steel slag, high iron phase silicate cement clinker, high belite sulfate cement clinker and palmitic acid into a steel ball mill for grinding until the specific surface area and 45 μm sieve residue are shown in Table 2, thereby obtaining a mixture 1; III. Take the waste residue and graphene and mix them thoroughly, add water until the mixed material is covered, stir for a certain period of time (see Table 2), and then directly dry to obtain the second mixed material for standby use; IV. Take fly ash, gypsum, solid waste and water reducing agent, and fully mix them with mixture 1 and mixture 2 to obtain a special cementitious material for microwave heating.
[0037] Table 1 Table 2 Comparative Example 1 Compared with the first group of Example 1, the only difference between this comparative example and the first group of Example 1 is that The fly ash and solid waste were replaced with steel slag of equal mass, and the rest of the process conditions remained unchanged.
[0038] Comparative Example 2 Compared with the first group of Example 1, the only difference between this comparative example and the first group of Example 1 is that Palmitic acid was replaced by high-belite sulphoaluminate cement clinker of equal mass, and the other process conditions remained unchanged.
[0039] Comparative Example 3 Compared with the first group of Example 1, the only difference between this comparative example and the first group of Example 1 is that The high-belite sulphoaluminate cement clinker and high-iron phase silicate cement clinker were replaced with steel slag of equal mass, and the other process conditions remained unchanged.
[0040] Comparative Example 4 Compared with the first group of Example 1, the only difference between this comparative example and the first group of Example 1 is that The caustic soda waste residue was replaced by solid waste of equal mass, and the other process conditions remained unchanged.
[0041] Comparative Example 5 The difference between this comparative example and the second group of Example 1 is that The fly ash and solid waste are replaced by steel slag of equal mass, the water reducer is replaced by desulfurized gypsum of equal mass, and the other process conditions remain unchanged.
[0042] Referring to the national standard GB 175-2023 "General Portland Cement", the relevant properties of the special cementitious materials for microwave heated concrete and the cementitious materials of comparative examples 1-5 were tested, and the microwave heating efficiency and resistivity of the formed slurry were tested.
[0043] The microwave heating efficiency is to prepare the gelling material into a 100*100*100mm pure pulp block, and put the pure pulp block into a KQ6000 adjustable industrial box-type microwave heating device. The power is set to 20kW and the frequency is 2.45GHz. The temperature is recorded after heating for ten minutes. The results are shown in the following table.
[0044] Table 3 It can be seen from Table 3 that the cementitious material obtained by adopting this scheme has excellent properties such as high early strength, high late strength, good electrical conductivity, high microwave heating efficiency, and good construction performance.
[0045] By comparing the first group of Example 1 with Comparative Example 1, it can be seen that fly ash and solid waste can make the particle grading of cementitious materials denser and improve the early and late strengths. The fine powder can act as a crystal nucleus to improve the early strength and reduce the setting time. At the same time, fly ash can also reduce the resistivity of the material and improve the conductivity.
[0046] By comparing the first group of Example 1 with Comparative Example 2, it can be seen that palmitic acid can improve the grinding efficiency and improve the particle grading, and the voids after the palmitic acid is heated and melted can increase the microwave heating performance.
[0047] From the comparison between the first group of Example 1 and Comparative Example 3, it can be seen that the combination of high-belite sulphoaluminate cement clinker and high-iron phase silicate cement clinker can effectively shorten the setting time, improve the early strength, and at the same time reduce the water demand of the cementitious material.
[0048] By comparing the first group of Example 1 with Comparative Example 4, it can be seen that caustic soda waste slag can stimulate the activity of steel slag to improve the early and late strength, and caustic soda waste slag can also reduce the resistivity by intercalating graphene or conducting itself through polarity.
[0049] By comparing the first group of Example 1 with Comparative Example 5, it can be seen that fly ash, solid waste and cementitious materials form a relatively complete gradation. By further reducing the water demand of the material through the water reducing agent, the setting time can be effectively shortened and the early and late strengths can be improved.
[0050] Application Example 1 The cementitious materials of each group in Example 1 and Comparative Examples 1-5 were added with aggregate and water to prepare concrete, and the molding mix ratio is shown in Table 4. The compressive strength of the concrete after standard curing for 28 days was tested with reference to GB / T 50107-2010 "Standard for Testing and Evaluation of Concrete Strength"; the air content and slump of the concrete were tested with reference to GB 50204-2015 "Concrete Structure Engineering Construction Quality Acceptance Code"; the resistivity of the concrete was tested with reference to ASTMC177-18; the microwave heating performance was tested by placing the standard test block after standard curing for 28 days into a KQ6000 adjustable industrial box-type microwave heating device, setting the power to 20 kW and the frequency to 2.45 GHz, and recording the temperature after heating for ten minutes, and the test results are shown in Table 5.
[0051] Table 4: Concrete mix proportions The coarse aggregate is limestone aggregate with a particle size of 2-5 mm and continuous grading; the fine aggregate is limestone sand with a continuous grading of 0-2 mm, and the water is tap water.
[0052] Table 5 As shown in Table 5, fly ash and solid waste can effectively fill the fine voids inside concrete, form precise accumulation, reduce water demand, and increase the strength and workability of concrete. At the same time, fly ash particles are small and can be quickly hydrated. The hydration products and solid waste can act as crystal nuclei to improve the early strength. Palmitic acid can effectively improve the grinding efficiency and make the particle grading of the powder more reasonable, thereby increasing the strength of concrete. The combination of high-belite sulphoaluminate cement clinker and high-iron phase silicate cement clinker can effectively shorten the setting time and is also the main source of strength. Compared with steel slag, it can also reduce the water demand of cementitious materials and reduce the porosity in concrete, thereby reducing the resistivity. Caustic soda waste slag can stimulate the activity of steel slag to improve the early and late strength. Caustic soda waste slag can also reduce the resistivity by intercalating graphene or conducting its own polarity. At the same time, caustic soda waste slag can also increase microwave heating performance. Water reducer is very important in the material. It can effectively reduce the water demand of the material and greatly reduce the porosity. At the same time, it can be combined with the filling benefits of fly ash and solid waste to greatly increase the strength of concrete and reduce the resistivity.
[0053] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A special cementitious material for microwave heating concrete, characterized in that: Calculated by mass, it includes the following components: 5-10 parts of fly ash; 30-45 parts of steel slag; 30-45 parts of high iron phase silicate cement clinker; 5-10 parts of high belite sulfate cement clinker; 5-10 parts of gypsum; 2-4 parts of waste residue; 3-5 parts of solid waste; Graphene 0.1-0.5 parts; Palmitic acid 0.5-1.5 parts; Water reducing agent 0.5-1.5 parts; The content of tetracalcium aluminate in the high-iron phase silicate cement clinker is greater than 20%, and the content of tricalcium aluminate is less than 3%; The content of dicalcium silicate in high-belite sulfate cement clinker is greater than 45%, and the content of calcium sulfoaluminate is 30-50%.
2. The special cementitious material for microwave heating concrete according to claim 1, characterized in that: The fly ash is the bottom ash collected by the flue gas purification system during the waste incineration process and settled at the bottom of the flue and chimney. The specific surface area of the fly ash is 600-1000m 2 / kg, calcium content is greater than 35%.
3. The special cementitious material for microwave heating concrete according to claim 1, characterized in that: The gypsum is desulfurized gypsum, and the content of calcium sulfate dihydrate in the desulfurized gypsum is greater than 94%, and the content of calcium carbonate is greater than 1%.
4. The special cementitious material for microwave heating concrete according to claim 1, characterized in that: The waste residue is waste residue generated during alkali production or alkali treatment, and the content of sodium hydroxide and potassium hydroxide in the waste residue is greater than 5%.
5. The special cementitious material for microwave heating concrete according to claim 1, characterized in that: The solid waste is dust collected during the limestone crushing process. The specific surface area of the solid waste is 500-800m 2 / kg.
6. The special cementitious material for microwave heating concrete according to claim 1, characterized in that: The graphene is multilayer graphene with a layer number greater than 15, and the particle size of the graphene is 0.05-2 mm.
7. The special cementitious material for microwave heating concrete according to claim 1, characterized in that: The palmitic acid is industrial grade palmitic acid with a melting point of less than 63° C. and a purity of more than 98%.
8. The special cementitious material for microwave heating concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylate water reducing agent with a water reducing rate greater than 45%.
9. A method for preparing a special cementitious material for microwave heating concrete as claimed in claim 1, characterized in that: The steps include: Ⅰ. Prepare the raw materials according to the composition ratio of claim 1 and set aside; Ⅱ. Take steel slag, high iron phase silicate cement clinker, high belite sulfate cement clinker and palmitic acid and put them into steel ball mill for grinding until the specific gravity is 270-320m 2 / kg, 45μm sieve residue is greater than 15%, and mixed material 1 is obtained; III. Take the waste residue and graphene and mix them thoroughly, add water until the mixed material is covered, stir thoroughly for 8-12 hours, and then directly dry to obtain the second mixed material for standby use; IV. Take fly ash, gypsum, solid waste and water reducing agent, and fully mix them with mixture 1 and mixture 2 to obtain a special cementitious material for microwave heating.
10. Use of the special cementitious material for microwave heating according to any one of claims 1 to 9 in the preparation of microwave-heatable concrete.
Citation Information
Patent Citations
Integrated cementing material for high-performance low-carbon concrete
CN117164311A
Phosphogypsum-based hydraulic material based on microwave chemical compounding as well as preparation and application of phosphogypsum-based hydraulic material
CN118324429A
Snow-melting and deicing concrete pavement based on conductive rubber composite material and preparation method of snow-melting and deicing concrete pavement
CN118480997A